THE Effect Of Competence And Emotional Intelligence On The Performance Of Pawon Nusantara Coffee Employees On The Island Of Java: Human Resource Management - Ira Nursehah; Chaerudin Chaerudin (Primanomics : Jurnal Ekonomi & Bisnis, 2022)
This study plans to look at and dissect the impact of skill and the capacity to appreciate people on a profound level on worker execution at Kopi Pawon Nusantara in Java Island. The exploration was directed utilizing expressive and confirmation techniques, specifically: gathering, introducing, dissecting and testing speculations and making ends and ideas. Test gathered with use recipe slovin , as well as likelihood examining procedure with basic irregular inspecting which then produces 133 examples from a population of 200 individuals. The logical strategy is utilized that is procedure investigation range scale and analysis track with assistance Methodof Succesive Stretch (MSI), Microsoft Succeed 2016 PC program and SPSS application rendition 21.Based on results examination that has been led concentrate on this demonstrate that Skill show the mean worth is 555.6 with rules concur . Knowledge Profound show the mean score is 542.7 with rules concur . Execution Representative show the typical worth is 523 with measures concur . Coefficient correlation Among the variables Environment Work and Workload obtained a score of 0.753 which means have a strong level, positive and significant correlation _ Among Competence and Emotional Intelligence. Influence by Partial Competence to Performance Employee by 0.860 more big from Intelligence emotional value _ of 0.086. So could declared that Competence more give contribution to Satisfaction Work compared with Emotional Intelligence . Influence simultaneous Competence to Performance Employee of 94.6% while the remaining 5.4% is other variables that are not researched .